International transmission of transitory and persistent monetary shocks under imperfect information - Torben M. Andersen; Niels C. Beier (Danmarks Nationalbank, 2004)
We analyze the transmission of monetary shocks in a new openeconomy macroeconomics model with one-period nominal contracts and imperfect information. Shocks may have transitory and persistent components, which only through accumulation of information over time becomes known. Responses to shocks are altered compared to the case of full information. There are persistent effects on international relative prices, and delayed exchange-rate overshooting is possible following a persistent shock. In some cases, there are (ex post) excess returns as a positive interest rate spread is accompanied by an appreciating currency (or vice versa). Lastly, it is demonstrated that staggering re-inforce persistence.
Keywords: E32; F41; 330; exchange rates; imperfect information; new open economy macroeconomics; nominal shocks; transitory and persistent shocks; persistence; Wechselkurstheorie; Schock; Geldpolitische Transmission; Unvollkommene Information; Theorie